The Role of Sulam Timbul MSMEs in Women's Economic Empowerment in Pakan Rabaa Village, South Solok - Dewi Nadia; Irwandi; Siska Elasta Putri; Syafriwaldi (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2026)
Women’s economic empowerment is a crucial element of sustainable development, particularly in rural areas that rely heavily on informal sectors and creative industries. One strategic approach to empowerment is through the development of Micro, Small, and Medium Enterprises (MSMEs) based on traditional crafts. In Solok Selatan Regency, embossed embroidery MSMEs serve as an important medium for enhancing women’s household income while preserving Minangkabau cultural heritage. This research employs a descriptive qualitative field research approach. Data were collected through observation, in-depth interviews, and documentation using both primary and secondary data sources. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that embossed embroidery MSMEs play a significant role in improving women’s skills, income, and economic independence. Embroidery activities not only provide economic benefits but also strengthen social capital, self-confidence, and women’s cultural identity. However, challenges remain, including limited capital, lack of design innovation, and inadequate digital marketing. Therefore, continuous support from government and stakeholders is necessary to ensure the sustainable development of embossed embroidery MSMEs as a model of women’s economic empowerment based on local wisdom